Anti-cancer activity of Kaempferia galanga L.–loaded polydopamine nanoparticles against colorectal cancer - Paweena Dana; Anukul Taweechaipaisankul; Yodsathorn Wongngam; Suttipun Sungsuwan; Walailuk Chonniyom; Saksorn Klibaim; Prattana Tanyapanyachon; Monthira Rattanatayarom; Onuma Phoraksa; Udom Asawapirom; Primana Punnakitikashem; Duangporn Polpanich; et al. (OpenNano)
Kaempferia galanga L. (KGL) is an aromatic ginger that has been used as a medicinal plant. Specifically, KGL possesses anti-inflammatory, antioxidant, anti-bacterial, and anti-cancer effects. However, the key component of KGL, ethyl p‑methoxy cinnamate (EPMC), is insoluble in water, resulting in low bioavailability. Hence, a nano-drug delivery system is used to enhance KGL activities. This study aimed to employ polydopamine (PDA) nanoparticles as a carrier for KGL delivery to improve its anti-cancer activity against colorectal cancer cells. PDA- and PDA nanoparticle–loaded KGL (PDA-KGL) were synthesized using a spontaneous oxidation process. The physicochemical properties of the PDA-KGL were characterized by dynamic light scattering methods. The anti-cancer activity of PDA-KGL was evaluated in HT-29, a colorectal cancer (CRC) cell line. Average hydrodynamic sizes of PDA and PDA-KGL were 236.2 ± 1.2 and 316.6 ± 2.0 nm, respectively, and the zeta potential of PDA and PDA-KGL were -23.0 ± 0.4 and -39.5 ± 0.6 mV, respectively. The morphology of PDA-KGL observed under TEM was spherical in shape. Anti-proliferative activity was monitored in HT-29 cells using MTT and 3D tumor spheroid assays. PDA-KGL strongly inhibited cell viability of HT-29 cells compared to free KGL and PDA treatments. PDA-KGL induced apoptosis in HT-29 cells as shown by an Annexin V binding assay. In addition, PDA-KGL suppressed the invasive ability of HT-29 cells compared to free KGL or PDA, which was determined by a transwell invasion assay. Taken together, it implies that PDA-KGL might be used as a nano-drug delivery approach for colorectal cancer treatment.